Perceptual Range, Targeting Ability, and Visual Habitat Detection by Greater Fritillary Butterflies Speyeria cybele (Lepidoptera: Nymphalidae) and Speyeria atlantis - MacDonald, Zachary G (J Insect Sci, 2019)
Butterflies are widely invoked as model organisms in studies of metapopulation and dispersal processes. Integral to such investigations are understandings of perceptual range; the maximum distance at which organisms are able to detect patches of suitable habitat. To infer perceptual range, researchers have released butterflies at varying distances from habitat patches and observed their subsequent flight behaviors. It is often assumed that butterflies rely on visual senses for habitat detection; however, this assumption has not been explicitly investigated. Here, we assess the extent and sensory determinants of perceptual range for the great spangled fritillary (Speyeria cybele (Fabricius, 1775)) and Atlantis fritillary (Speyeria atlantis (W.H. Edwards, 1862)). This was achieved by experimentally releasing butterflies over open water at various distances from a lake island, representing an isolated habitat patch in a dichotomous habitat-matrix landscape. To infer whether butterflies rely on vision for habitat detection, we exposed a subset of butterflies to a series of intense light flashes before release to induce flash blindness (bleaching of photoreceptive rhodopsins) without affecting olfaction. Flashed individuals were 30.1 times less likely to successfully navigate to the target island after release, suggesting butterflies rely primarily on visual senses to navigate fragmented landscapes. For unflashed butterflies, the likelihood of successful navigation decreased by a factor of 2.1 for every 10 m increase in release distance. However, no specific distance threshold for perceptual range was observed. We therefore suggest that perceptual range is best viewed as a continuum of probabilities (targeting ability), reflecting the likelihood of habitat detection across a range of distances.